Average Error: 0.0 → 0.0
Time: 4.8s
Precision: 64
${x}^{2} - {x}^{\left(-2\right)}$
${x}^{2} - {x}^{\left(-2\right)}$
{x}^{2} - {x}^{\left(-2\right)}
{x}^{2} - {x}^{\left(-2\right)}
double f(double x) {
double r37978957 = x;
double r37978958 = 2.0;
double r37978959 = pow(r37978957, r37978958);
double r37978960 = -r37978958;
double r37978961 = pow(r37978957, r37978960);
double r37978962 = r37978959 - r37978961;
return r37978962;
}


double f(double x) {
double r37978963 = x;
double r37978964 = 2.0;
double r37978965 = pow(r37978963, r37978964);
double r37978966 = -r37978964;
double r37978967 = pow(r37978963, r37978966);
double r37978968 = r37978965 - r37978967;
return r37978968;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

${x}^{2} - {x}^{\left(-2\right)}$
2. Final simplification0.0

$\leadsto {x}^{2} - {x}^{\left(-2\right)}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "pow(x,2)-pow(x,-2)"
(- (pow x 2.0) (pow x (- 2.0))))